2014
DOI: 10.4102/ajlm.v3i2.248
|View full text |Cite
|
Sign up to set email alerts
|

Weighing the costs: Implementing the SLMTA programme in Zimbabwe using internal versus external facilitators

Abstract: BackgroundIn 2010, the Zimbabwe Ministry of Health and Child Welfare (MoHCW) adopted the Strengthening Laboratory Management Toward Accreditation (SLMTA) programme as a tool for laboratory quality systems strengthening.ObjectivesTo evaluate the financial costs of SLMTA implementation using two models (external facilitators; and internal local or MoHCW facilitators) from the perspective of the implementing partner and to estimate resources needed to scale up the programme nationally in all 10 provinces.MethodsT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…We identified 28 published manuscripts focusing on the SLMTA programme, 1,7–33 including 26 published concurrently with this article, 1,7-20,22-31,33 one previously-published article summarising the development and methodology of the SLMTA programme 32 and one previously-published study regarding SLMTA implementation in Lesotho 21 (Table 1). Six papers presented experiences from a single laboratory 7,10,17,26,28 or a single hospital, 9 14 presented data from two to 45 laboratories within a single African country, 8, 12,–15,18,–22,25,29–31 one discussed activities in two Southeast Asian countries, 23 one covered data from four countries in the Caribbean Region 11 and six had a general or global focus.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We identified 28 published manuscripts focusing on the SLMTA programme, 1,7–33 including 26 published concurrently with this article, 1,7-20,22-31,33 one previously-published article summarising the development and methodology of the SLMTA programme 32 and one previously-published study regarding SLMTA implementation in Lesotho 21 (Table 1). Six papers presented experiences from a single laboratory 7,10,17,26,28 or a single hospital, 9 14 presented data from two to 45 laboratories within a single African country, 8, 12,–15,18,–22,25,29–31 one discussed activities in two Southeast Asian countries, 23 one covered data from four countries in the Caribbean Region 11 and six had a general or global focus.…”
Section: Resultsmentioning
confidence: 99%
“…Six papers presented experiences from a single laboratory 7,10,17,26,28 or a single hospital, 9 14 presented data from two to 45 laboratories within a single African country, 8, 12,–15,18,–22,25,29–31 one discussed activities in two Southeast Asian countries, 23 one covered data from four countries in the Caribbean Region 11 and six had a general or global focus. 1,16,23,24,32,33 In total, these studies included detailed information on SLMTA implementation in 211 laboratories in 18 countries.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in Zimbabwe, Shumba et al found that it cost less over the long term to engage and train local quality managers as auditors, trainers and mentors than to import international consultants to do the job. 10 Minimizing costs is essential because programmes that require unacceptable levels of resource commitment are unsustainable. 6 …”
Section: Discussionmentioning
confidence: 99%
“…This was done through the use of an inventory of all resources and payments made for the programme. 8 Costs calculated included: the three training courses which were attended by the mentors; mentorship costs such as salaries, travel and lodging, internet access and laptops; and supervisory costs (Table 1). This analysis was limited to the direct costs of providing mentorship and supervision only.…”
Section: Research Methods and Designmentioning
confidence: 99%